Exploration of Poetic Texts by Foreign Students Within the Framework of Modern Poetic Discourse - O. V. Medukha (Дискурс профессиональной коммуникации, 2021)
The article describes the peculiarities of the analysis of the poetic Russian text while teaching foreign students. Studying poetic texts enables students not only to learn a foreign language, expand vocabulary but also deepen the understanding of the country’s culture. Regardless of the foreign students’ language level, the use of literary texts in class is really efficient as it helps to concentrate on both information exchange and the process of mutual verification of subjective experience-impression. Discussion of poetry encourages students’ active non-linear interaction with the target language as well as contributes to their critical interaction with a variety of texts, including literary and scientific ones. The communicative situation that arises during distance learning is analyzed within the framework of poetic, poet-related and institutional discourses. When teaching poetry, the author applies Google Street View technology to provide an interactive panoramic view of the points the poets refer to in their works. The article offers methodological notes aimed to contribute to effective work with students whose proficiency in the target language is at B2 level and higher. The article also presents an example of the analysis of a poetic passage and conclusions concerning the students’ interaction with it.